A proteomic study of mesenchymal stem cells from equine umbilical cord - Maia, Leandro [UNESP]; de Moraes, Carolina Nogueira [UNESP]; Dias, Marianne Camargos [UNESP]; Martinez, Julia Bauzá; Caballol, Antonia Odena; Testoni, Giorgia; de Queiroz, Carla Martins [UNESP]; Peña, Ramón Díaz; Landim-Alvarenga, Fernanda C. [UNESP]; de Oliveira, Eliandre (Elsevier, 2017)
To the best of our knowledge, this is the first study describing the proteome of equine umbilical cord intervascular matrix mesenchymal stem cells (UCIM-MSCs) in a global and functional manner. The aim of this work was to analyze the proteome of previously characterized UCIM-MSCs to determine protein abundance and classify the identified proteins according to Gene Ontology (GO) terms. Protein classification analysis according to biological process, molecular function and cellular component was performed using the PANTHER (Protein ANalysis THrough Evolutionary Relationships) Classification System, which revealed enrichment for 42 biological processes, 23 molecular functions and 18 cellular components. Protein abundance was estimated according to the emPAI method (Exponential Modified Protein Abundance Index). The two most abundant proteins in the proteome of UCIM-MSCs were the cytoskeletal proteins actin and vimentin, which have important roles in cell stability and motility. Additionally, we identified 14 cell surface antigens. Three of them, CD44, CD90 and CD105, had been previously validated by flow cytometry. In the present study, we also identified important information about the biological properties of UCIM-MSCs such as differentiation potential, low immunogenicity (low MHC-II expression) and chromosomal stability, which reinforces their use for cell therapy. Together with the proteomic findings, this information allowed us to infer the functional relevance of several activities related to primary metabolic processes, protein synthesis, production of vesicle coats, vesicle-mediated transport and antioxidant activity. In addition, the identification of different cell surface markers may help establish an immunophenotypic panel suitable for the characterization of MSCs from equine fetal membranes.
Keywords: Horse; Mass spectrometry; MSCs; Protein; Proteomics